ATP-fuelled self-assembly to regulate chemical reactivity in the time domain. Issue 6 (2nd January 2020) - Cardona, Maria A.; Prins, Leonard J.
Abstract : The addition of ATP under dissipative conditions to a complex mixture causes the transient upregulation of hydrazone-bond formation. Abstract : Here, we exploit a small biomolecule – ATP – to gain temporal control over chemical reactivity in a synthetic system composed of small self-assembling molecules and reactants. The approach relies on the capacity of ATP to template the formation of amphiphile-based assemblies. The presence of the enzyme alkaline phosphatase causes a gradual decrease in the ATP-concentration in time and, consequently, a spontaneous dissociation of the assemblies. The uptake of apolar reactants in the hydrophobic domain of the assemblies leads to an enhancement of the reaction rate. It is shown that ATP-triggered self-assembly causes the selective upregulation of one out of two hydrazone-bond formation reactions that take place concurrently in the system. This leads to an inversion in the product ratio, which, however, is transient in nature because the upregulated reaction spontaneously reverts to its basal low reaction rate once the ATP has been consumed by the enzyme. Overall, the results demonstrate the potential of chemically-fuelled self-assembly under dissipative conditions to gain temporal control over reactivity in complex chemical systems.